THE EFFECT OF BRAND IMAGE, BRAND TRUST AND BRAND PERSONALITY TOWARDS CUSTOMER LOYALTY (A STUDY ON SAMSUNG SMARTPHONE USERS IN UNIVERSITAS BRAWIJAYA) - Luqman Aziz Mahardhika Indrajati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This research aims to discover the impact of Brand Image, Brand Trust and Brand Personality towards Customer Loyalty of Samsung Smartphone user in Brawijaya University area. This explanatory research explains the relationship and the influence between one variable and another through hypothesis testing. This research collected sample of 160 respondents via online survey. The sample of this research consists of the respondents are currently use Samsung Smartphone and the students from Brawijaya University. The data analysis used in this research was the Multiple Linear Regression Analysis. From the results of testing seven hypotheses, it can be concluded that the variable of Brand Image, Brand Trust and Brand Personality have a significant influence on the Customer Loyalty. This research implied that proper maintenance of the Brand Image, Brand Trust and Brand Personality of Samsung Smartphone would increase their consumers' Customer Loyalty.Keywords: Brand Image, Brand Trust and Brand Personality, Customer Loyalty